Anastomotic leakage treatment with endoscopic stent after small bowel transplantation in an infant - Baran, Maşallah; Aksoy, Betül; Öztan, Onur; Yıldız, Coşkun; Turhan, Soysal; Çağan Appak, Yeliz; Tuğmen, Cem; Karaca, Cezmi (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Baran M, Aksoy B, Öztan MO, et al. Anastomotic leakage treatment with endoscopic stent after small bowel transplantation in an infant. Turk J Gastroenterol 2020; 31(9): 667-70.